Given:
A line passes through (-5,-3) and perpendicular to
.
To find:
The equation of the line.
Solution:
We have,
![y=-\dfrac{9}{4}x-5](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B9%7D%7B4%7Dx-5)
On comparing this equation with slope intercept form, i.e.,
, we get
![m_2=-\dfrac{9}{4}](https://tex.z-dn.net/?f=m_2%3D-%5Cdfrac%7B9%7D%7B4%7D)
It means, slope of this line is
.
Product of slopes of two perpendicular lines is always -1.
![m_1\times m_2=-1](https://tex.z-dn.net/?f=m_1%5Ctimes%20m_2%3D-1)
![m_1 \times \left(-\dfrac{9}{4}\right)=-1](https://tex.z-dn.net/?f=m_1%20%5Ctimes%20%5Cleft%28-%5Cdfrac%7B9%7D%7B4%7D%5Cright%29%3D-1)
![m_1=\dfrac{4}{9}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B4%7D%7B9%7D)
Slope of required line is
and it passes through the point (-5,-3). So, the equation of the line is
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
where, m is slope.
![y-(-3)=\dfrac{4}{9}(x-(-5))](https://tex.z-dn.net/?f=y-%28-3%29%3D%5Cdfrac%7B4%7D%7B9%7D%28x-%28-5%29%29)
![y+3=\dfrac{4}{9}(x+5)](https://tex.z-dn.net/?f=y%2B3%3D%5Cdfrac%7B4%7D%7B9%7D%28x%2B5%29)
![9(y+3)=4(x+5)](https://tex.z-dn.net/?f=9%28y%2B3%29%3D4%28x%2B5%29)
![9y+27=4x+20](https://tex.z-dn.net/?f=9y%2B27%3D4x%2B20)
![27-20=4x-9y](https://tex.z-dn.net/?f=27-20%3D4x-9y)
![7=4x-9y](https://tex.z-dn.net/?f=7%3D4x-9y)
Therefore, the equation of required line is
.
Answer:
AB=29; BC=27
Step-by-step explanation:
So they told us AB=4x+9 and that BC=5x+2, and AC=56 , now to help with the question you can draw this information on a number line. Now on a number you can see that basically AC=AB+BC.
So you would write it as such,,
4x+9+5x+2=56
Combine like terms
9x+11=56
Now you have to isolate the x by itself but first get rid of the 11.
9x+11-11=56-11
You would get
9x=45
Here you can divide 9 by both sides to isolate x.
9x/9=45/9
{x=5}
Now to find the value for both substitue x in the equations for both
1. AB=4x+9 where x is 5
4(5)+9 =AB
20+9 =AB
29=AB
You would do the same with BC
2. BC= 5x+2 where x is 5
5(5)+2= BC
25+2= BC
27=BC
If you want to check your answers you can just substitute x for 5 in the first equation we did where AC=AB+BC
Answer:
<h3>
![\boxed{ \bold{ 6x + 11}}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cbold%7B%206x%20%3C%2Fstrong%3E%3Cstrong%3E%2B%3C%2Fstrong%3E%3Cstrong%3E%20%3C%2Fstrong%3E%3Cstrong%3E11%7D%7D)
</h3>
Step-by-step explanation:
![\mathsf{3(4x + 1) - 2(3x - 4)}](https://tex.z-dn.net/?f=%20%5Cmathsf%7B3%284x%20%2B%201%29%20-%202%283x%20-%204%29%7D)
Distribute 3 through the parentheses
![\mathsf{12x + 3 -2(3x - 4)}](https://tex.z-dn.net/?f=%20%5Cmathsf%7B12x%20%2B%203%20-2%283x%20-%204%29%7D)
Distribute 2 through the parentheses
⇒![\mathsf{12x + 3 - 6x + 8}](https://tex.z-dn.net/?f=%20%5Cmathsf%7B12x%20%2B%203%20-%206x%20%2B%208%7D)
Collect like terms
⇒![\mathsf{6x + 11}](https://tex.z-dn.net/?f=%20%5Cmathsf%7B6x%20%2B%2011%7D)
Hope I helped!
Best regards!!
Answer:
x = 6.125
Step-by-step explanation:
y = -2 + 34
so
-2x + 34 = 6x - 15
<u>+2x +2x </u>
34 = 8x - 15
<u>+15 +15</u>
49 = 8x
<em><u>x = 6.125</u></em>
plz mark as brianliest if correct!!!